Evaluating DC-DC Buck Converter Efficiency with MOSFET and GaN-FET Technology - Kaur, Puneet (Journal of Scientific Research, 2025)
This paper assesses the efficiency of DC-DC buck converters utilizing both MOSFET and GaN-FET technology. An analysis is conducted on single-phase switched capacitor buck converter equipped with GaN FETs, highlighting its capability to operate at higher frequencies due to the rapid switching speeds of GaN FETs. This feature results in a decreased size of passive components in comparison to traditional buck converters. Additionally, the specifications for the inductor are also examined. To demonstrate the advantages of GaN FETs over MOSFETs in DC-DC converters, the performance of the GaN-FET based converter is compared with that of a traditional MOSFET-based converter. Key performance metrics evaluated includes output voltage, inductor current ripple, voltage stresses across semiconductor devices, power losses, and overall efficiency. The results indicate that the GaN-FET based converter achieves a lower output voltage at higher duty cycles, reducing losses associated with small duty cycles. Additionally, the proposed converter demonstrates superior performance across all evaluated parameters, reinforcing the efficiency benefits of GaN-FET technology in DC-DC buck converters.